2014
DOI: 10.5194/amt-7-919-2014
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic ash infrared signature: porous non-spherical ash particle shapes compared to homogeneous spherical ash particles

Abstract: Abstract. The reverse absorption technique is often used to detect volcanic ash clouds from thermal infrared satellite measurements. From these measurements effective particle radius and mass loading may be estimated using radiative transfer modelling. The radiative transfer modelling usually assumes that the ash particles are spherical. We calculated thermal infrared optical properties of highly irregular and porous ash particles and compared these with mass-and volume-equivalent spherical models. Furthermore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 41 publications
0
42
0
Order By: Relevance
“…It has been shown by Kylling et al (2014) that the assumption of spherical particles may underestimate the retrieved ash mass loading by tens of percent compared to porous nonspherical particles. Also, no internal mixing of ash and ice was included.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by Kylling et al (2014) that the assumption of spherical particles may underestimate the retrieved ash mass loading by tens of percent compared to porous nonspherical particles. Also, no internal mixing of ash and ice was included.…”
Section: Discussionmentioning
confidence: 99%
“…Stevenson et al (2015) discuss potential errors in satellite retrievals by using cryptotephra data to speculate that larger particles exist in dispersing ash clouds (although no atmospheric observations are presented) and claim through modelling studies that current retrieval schemes (all of them) underestimate mass loadings because of the dense sphere as- sumption and lack of sensitivity to particles with diameters > 10 µm. Estimating precision in retrievals is difficult because of the uncertainties in the input parameters, such as the complex index of refraction, the size distribution, and the shapes of the particles, although shape is generally found to result in the smallest discrepancy of the input parameters, with theoretical simulations showing differences in the range of 10-40 % (Yang et al, 2007b;Kylling et al, 2014). An additional problem with estimating precision due to shape is that apart from having no observations, the effect of their statistical orientation in space and the distribution of the shapes as a function of particle size is unknown and potentially large.…”
Section: Error In Ash Retrievalsmentioning
confidence: 99%
“…Wen and Rose (1994) studied the volcanic eruption at Crater Peak, Alaska, in 1992 and found that total mass is doubled due to changes in ash particle size distribution. Kylling et al (2014) found a 30 % difference in total mass due to the assumed ash particle shape. The effect of meteorological clouds is seen to both increase and decrease the retrieved ash mass loading (Kylling et al, 2015).…”
Section: Satellite Datamentioning
confidence: 99%